An unusual case of an isolated, incarcerated appendix epiploica inguinal hernia and laparoscopic mesh herniorrhaphy - Yagan Pillay; Maryna Reshetar (International Journal of Abdominal Wall and Hernia Surgery)
An isolated appendix epiploica (AE) inguinal hernia remains a rare surgical entity despite laparoscopic herniorrhaphy and improved intra peritoneal visualization. The surgical disposition of the AE remains controversial with proponents for both excision and conservative management. The paucity of data, based only on case reports precludes definite guidelines in their management. The presence of infection, organ ischemia, surgeon experience, and biological mesh availability all play a role in the management of this type of hernia. We present a rare case report with a viable incarcerated, AE inguinal hernia and its laparoscopic excision, and hernia repair. This is only the third such case report in the published literature to date.